Numerical Calculation of an Asymmetric Supply Function Equilibrium with Capacity Constraints - Pär Holmberg (Uppsala University, Department of Economics, 2005)
Producers submit committed supply functions to a procurement auction, e.g. an electricity auction, before the uncertain demand has been realized. In the Supply Function Equilibrium(SFE), every firm chooses the bid maximizing his expected profit given the bids of the competitors. In case of asymmetric producers with general cost functions, previous work has shown that it is very difficult to find valid SFE. This paper presents a new numerical procedure that can solve the problem. It comprises numerical integration and an optimization algorithm that searches an end-condition. The procedure is illustrated by an example with three asymmetric firms.
urn:nbn:se:uu:diva-20122
Keywords: C61; D43; D44; L11; L13; L94; 330; Supply function equilibrium; uniform-price auction; numerical integration; oligopoly; asymmetry; capacity constraint; wholesale electricity market; Angebot; Auktion; Oligopol; Elektrizität; Dynamisches Gleichgewicht